Oxidative stress in dry age-related macular degeneration and exfoliation syndrome. (February 2015) - Chiras, Dimitrios; Kitsos, George; Petersen, Michael B.; Skalidakis, Iosif; Kroupis, Christos
Abstract Oxidative stress refers to cellular or molecular damage caused by reactive oxygen species, which especially occurs in age-related conditions as a result of an imbalance between the production of reactive oxygen species and the antioxidant defense response. Dry age-related macular degeneration (AMD) and exfoliation syndrome (XFS) are two common and complex age-related conditions that can cause irreversible vision loss. Two subtypes of AMD, which is the leading cause of blindness in the Western world, exist: the most prevalent dry type and the most severe wet type. Early dry AMD is characterized by formation of drusen, which are sub-retinal deposits, in the macular area and may progress to geographic atrophy with more dramatic manifestation. XFS is a systemic disorder of the extracellular matrix characterized by the accumulation of elastic fibrils that leads, in most cases, to glaucoma development with progressive and irreversible vision loss. Due to the aging population, the prevalence of these already-widespread conditions is increasing and is resulting in significant economic and psychological costs for individuals and for society. The exact composition of the abnormal drusen and XFS material as well as the mechanisms responsible for their production and accumulation still remain elusive, and consequently treatment for both diseases is lacking. However, recent epidemiologic, genetic and molecular studies support a major role for oxidative stress in both dry AMD and XFS development. Understanding the early molecular events in their pathogenesis and the exact role of oxidative stress may provide novel opportunities for therapeutic intervention for the prevention of progression to advanced disease.